Is continuous proximal adductor canal analgesia with a periarticular injection comparable to continuous epidural analgesia for postoperative pain after Total Knee Arthroplasty? A retrospective study - Willett, Amy (Rom J Anaesth Intensive Care, 2019)
BACKGROUND: The classic adductor canal block (ACB) is a regional technique that aims to introduce local anesthetic to the saphenous nerve as it traverses the adductor canal. It offers the benefit of preserved quadriceps strength, and is ideal for rehabilitation. Proximal ACB (PACB) allows the operator to place the block away from the surgical site, permitting preoperative placement. Our primary outcome was total opioid consumption; secondary outcomes included the highest numerical rating scale scores and total gait distance at the indicated time intervals. QUESTIONS/PURPOSES: We asked: 1) Does a Continuous Proximal ACB block with Periarticular knee injection (PACB) provide better analgesia than a Continuous Epidural (CSE)?; 2) Do PACB catheter patients do better with physical therapy compared to CSE patients?; 3) Are PACB patients discharged earlier than CSE patients? METHODS: With IRB approval we performed a retrospective chart review of patients who had underwent primary total knee arthroplasty between October 2015 and September 2016. The selected patients (n = 151) were divided into two groups: CSE group, 72 patients who received a continuous epidural catheter and the PACB group, 79 patients who received at PACB with Periarticular injection. The CSE group received a single-segment combined spinal epidural (CSE) in the operating room. The epidural catheter infusion was started with 0.1% ropivacaine at 8 mL/hour to 14 mL/hour during the post-operative period. The PACB group received a proximal adductor canal catheter with 20 ml of 0.5 % ropivacaine and maintained with ropivacaine 0.2% at 8 ml to 14 ml post operatively. Total opioid consumption, highest numeric rating scores and total gait distance travelled were recorded upon discharge from the PACU and completion of postoperative day (POD) 0, 1, and 2. RESULTS: We found that the median cumulative morphine consumption was significantly higher in the CSE group compared to the PACB group (194 (0–498) versus 126 (0–354) mg, p = 0.012), a difference that was most notable on POD 1 (84 (16–243) versus 60 (5–370) mg, p = 0.0001). Mean hospital length of stay was also shorter in the PACB group (2.6 ± 0.67 versus 3.0 ± 1.08 days, p = 0.01). CONCLUSION: PACB group used significantly lower morphine consumption compared to the CSE group; they were better participants during physical therapy and achieved longer gait distances. The mean hospital length of stay was also shorter in the PACB group